Model Pembelajaran IMPLEMENTASI MODEL PEMBELAJARAN VAK DAN PBL DALAM MENINGKATKAN HASIL BELAJAR SISWA SMP MUHAMMADIYAH 33 JAKARTA - Retno Nengsih (LP3M STKIP Muhammadiyah Muara Bungo, 2021)
The purpose of this study was to analyze the results of learning mathematics in the visual, auditory, and kinesthetic (vak) learning model and the problem-based learning (pbl) model for students of SMP Muhammadiyah 33 Jakarta. The research method used in this research is a quasi-experimental method. The sampling technique used was cluster sampling and simple random sampling. The instrument for collecting data was a test with 8 essays. The data analysis technique used is descriptive analysis technique and data requirements test. Test data requirements used are normality test and homogeneity test. In normality test, obtained sig. > α, means that data in the experimental and control class are normally distributed. In homogeneity test, obtained sig.> α, that is, both data have homogeneous variants. Furthermore, the hypothesis is tested using a free (independent) sample t-test. Based on the calculation, obtained sig. <α and tcount> ttable, so H0 is rejected and the mathematics learning outcomes of students who are given visual, auditory, and kinesthetic (vak) learning models are higher than learning outcomes who are given problem-based learning models. Thus, the VAK learning model is better than the PBL learning model for mathematics learning outcomes of SMP Muhammadiyah 33 Jakarta. Keywords: vak learning model, pbl learning model, efforts to improve learning outcomes.